Pigeon Point, Tobago - Yhap, Christine (C.P.P.P. Ltd.,[Trinidad and Tobago], 2011)
This postcard offers a scenic view of the jetty at Pigeon Point Beach in Tobago. Postcard number F2.
Colour: Coloured; Style: Landscape; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Beaches--Trinidad and Tobago; Bathing beaches--Trinidad and Tobago; Seashore--Trinidad and Tobago; Coasts--Trinidad and Tobago; Coconut palm--Trinidad and Tobago; Jetties--Trinidad and Tobago; Piers--Trinidad and Tobago; Signs and signboards--Trinidad and Tobago; Thatched roofs--Trinidad and Tobago; [1995]